The Challenge of Coming Out to Providers by Gay and Bisexual Men With Prostate Cancer: Qualitative Results from the Restore Study. Issue 3 (3rd July 2021) - West, William; Torres, Maria Beatriz; Mitteldorf, Darryl; Capistrant, Benjamin D.; Konety, Badrinath R.; Polter, Elizabeth; Rosser, B. R. Simon
Abstract: This study investigates the experience of communicating sexual orientation by gay, bisexual and men who have sex with men (GBM) to physicians involved in their prostate cancer care. Methodology consisted of qualitative analysis conducted on 30 in-depth interviews of GBM recruited from a national online cancer support site. Results revealed four key strategies around sexual disclosure. These ranged from explicitly outing themselves to selective or non-disclosure. Disclosures had unpredictable multiple outcomes ranging from increased trust in the patient-physician relationship to seeking alternate treatment. We concluded competent care is achieved when physicians know their patient's sexual orientation, and are trained in them.